واقع قطاع التأمين في سورية ودوره في التنمية الاقتصادية والاجتماعية - ديوب, محمد معن; عبد الحي, عماد الدين; أحمد, سامر محمد (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يتناول هذا البحث قِطَاعاً مُهمّاً في الاقتصاد الوطني وهو قطاع التأمين، وإلقاء الضوء على دوره في التنمية الاقتصادية والاجتماعية في سورية. ويهدف البحث إلى بيان الفوائد الكبيرة التي يقدمها التأمين للفرد والمجتمع والشركات. ويناقش البحث أعمال المؤسسة العامة السورية للتأمين خلال فترة الاحتكار، وأعمال شركات التأمين الخاصة التي تعمل في السوق المحلية، والمنافسة المتوقعة بينهم. كما يهدف البحث إلى تحليل أقساط التأمين وبيان معدلات النمو في جميع الفروع. وأخيراً سيصل البحث إلى نتائج مهمة وبعض التوصيات لتطوير قطاع التأمين السوري. This research studies an important sector of the national economy, which is the insurance sector and to shed light at the role which insurance plays in supporting the economic and social development in Syria. The research aims to showing the huge benefits which insurance provides to the individual, community, and companies. Also, this research discusses the works of the Syrian Insurance Company during the monopoly period, and works of the private insurance companies which work in the local market, and the expected competition between them. The research aims to analyze the insurance installments, and to show the rates of growth in all branches. Finally, the study reaches important results and many recommendations to develop insurance sector.